Accurate EH Modelling and Achievable Information Rate for SLIPT Systems with Multi-Junction Photovoltaic Receivers - Shanin, Nikita; Ajam, Hedieh; Papanikolaou, Vasileios; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2024)
In this paper, we study simultaneous lightwave information and power transfer (SLIPT) systems employing photovoltaic optical receivers (RXs). We consider the case, where the optical RX is illuminated by ambient light and an intensity-modulated information-carrying free space optical (FSO) signal. To overcome the possible absence of ambient light, e.g., indoors or at night, we additionally assume that the optical RX receives a dedicated energy-bearing broadband optical signal. Additionally, to efficiently harvest energy from broadband light, we propose a novel optical RX based on multi-junction photovoltaic cells. Exploiting the analysis of the equivalent two-diode electrical circuit for the multi-junction photovoltaic RX, we carefully model the current flow through the photovoltaic cell and derive an accurate energy harvesting (EH) model. Furthermore, we also derive novel approximate EH models for the two cases, where the optical RX is equipped with a single and multiple p-n junctions, respectively. Next, we derive the distribution of the transmit information signal that maximizes the achievable information rate and, for a practical pulse amplitude modulated information signal, we determine the symbol error rate at the RX. We validate the proposed EH models by circuit simulations and show that the photovoltaic RXs saturate for high received signal powers. For single-junction RXs, we compare the proposed EH model with two well-known baseline EH models, which are based on maximum point tracking and a single-diode electrical circuit, respectively. We demonstrate that, in contrast to the proposed EH model, both baseline EH models are not able to fully capture the non-linear behavior of photovoltaic RXs. Moreover, our results reveal that, since multi-junction RXs allow a more efficient allocation of the optical power, they are more robust against saturation, and thus, are able to harvest significantly more power and achieve higher data rates than RXs employing a single p-n junction. Finally, we highlight a tradeoff between the information rate and harvested power in SLIPT systems and demonstrate that the proposed transmit signal distribution yields significantly higher achievable information rates compared to uniformly distributed transmit signals, which are optimal for linear optical information RXs.
CRIS-Team Scopus Importer:2024-07-19
Keywords: non-linear energy harvesting; optical receiver design; optical wireless communication; photovoltaics; SLIPT